HUBUNGAN KERAPATAN VEGETASI DAN STOK KARBON BAGIAN ATAS PERMUKAAN TANAH PADA HUTAN MANGROVE DI DESA SUNGAI KUPAH - Erwan, Erwan; Anshari, Gusti Zakaria; Hardiansyah, Gusti (Universitas Tanjungpura, 2025)
The carbon storage in mangrove forest plays a crucial role in climate change mitigation. Sungai kupah village is an ecotourism village engaged in mangrove forest tourism restoration. Therefore, the government